2014
DOI: 10.1021/es405804m
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI) Adsorption and Reduction by Humic Acid Coated on Magnetite

Abstract: Easily separable humic acid coated magnetite (HA-Fe3O4) nanoparticles are employed for effective adsorption and reduction of toxic Cr(VI) to nontoxic Cr(III). The adsorption and reduction of Cr(VI) is effective under acidic, neutral, and basic pH conditions. The chromium adsorption nicely fits the Langmuir isotherm model, and the removal of Cr(VI) from aqueous media by HA-Fe3O4 particles follows pseudo-second-order kinetics. Characterization of the Cr-loaded HA-Fe3O4 materials by X-ray absorption near edge str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
179
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(190 citation statements)
references
References 52 publications
6
179
1
4
Order By: Relevance
“…Unfortunately, most magnetic sorbents that are based on MNPs have several deficiencies such as leaching under acidic conditions, being susceptible to autoxidation and toxicity. Therefore, protection of the surface of the bare MNPs can be performed to reduce these undesirable features [17]. For this purpose, MNPs are embedded in a polymeric, hybrid or inorganic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most magnetic sorbents that are based on MNPs have several deficiencies such as leaching under acidic conditions, being susceptible to autoxidation and toxicity. Therefore, protection of the surface of the bare MNPs can be performed to reduce these undesirable features [17]. For this purpose, MNPs are embedded in a polymeric, hybrid or inorganic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Very stable Cr(III)-organic complexes form when Cr(VI) is reduced by soil organic matter [28,30]. Effective sorption and reduction of Cr(VI) by humic acid coated on magnetite has been recently demonstrated by XANES [31]. This work demonstrated that humic acid (HA) was responsible of Cr(VI) reduction while the valence state of the iron in magnetite remained unchanged.…”
Section: Abiotic Redox Processesmentioning
confidence: 80%
“…Due to this, the removal of Cr(VI) was found to be effective at Fe(II) dosages lower than the aforementioned 1:3 molar ratio ([Cr(VI)]:[Fe(II)]) [21,22]. The kinetics of a combined reduction by the co-presence of Fe(II) and HAs are hereby different from the kinetics of experiments where only Fe(II) or only HAs were available [22,23]. It is claimed that this effect is dependent on the specific type of humic substance [22] and it is also limited by the lower solubility of Fe(III) at higher pH values, which would lead to a precipitation of ferric hydroxide(s), so that no further recycling of Fe can take place [24].…”
Section: Introductionmentioning
confidence: 86%
“…These results are not in good agreement with the results reported by other researchers. Jiang et al [23] showed that HAs by themselves are capable of reducing Cr(VI) to Cr(III). Prior to the tests with Fe(II), several batch tests were conducted to verify if the presence of HAs influences the oxidation state of chromium.…”
Section: Removal Of Chromium In the Presencementioning
confidence: 99%